Levosimendan as a treatment for acute renal failure associated with cardiogenic shock after hip fracture - Hinojosa,Fabiola Quinteros (2017)
Abstract Inotropic drugs are part of the treatment of heart failure; however, inotropic treatment has been largely debated due to the increased incidence of adverse effects and increased mortality. Recently levosimendan, an inotropic positive agent, has been proved to be effective in acute heart failure, reducing the mortality and improving cardiac and renal performance. We report the case of a 75-year-old woman with history of heart and renal failure and hip fracture. Levosimendan was used in preoperative preparation as an adjuvant therapy, to improve cardiac and renal function and to allow surgery.